Assembling Shinto: Buddhist approaches to kami worship in medieval Japan - Andreeva, Anna (Harvard East Asian monographs, 2017)
Part I. Mt. Miwa and the Yamato landscape : The ancient cultic site -- The sacred mountain -- From Izumo to Yamato -- Of snakes and women -- The Omiwa family and the early Yamato rulers -- Miwa as a cultural and economic centre -- The Omiwa shrine and its festivals -- The Omiwa jinguji -- Within the imperial system -- Temple networks in southern Yamato -- In the shadow of Kofukuji -- Control of the land -- At the crossroads of pilgrimage circuits -- Hasedera -- Kofukuji monks and Mt. Muro -- Esoteric Buddhism at Muro -- Tonomine and Yoshino-Kinpusen -- Part II. Holy men and Buddhist monks at Miwa : Miwa Bessho -- Holy men of Miwa in the medieval sources -- Roaming around Muro, Kinpusen, and Tonomine -- Kakuban's formula -- Miwa Bessho, Byodoji -- "Country bumpkins" in search of enlightenment -- Saidaiji -- Saidaiji and Eizon -- Saidaiji monks at Miwa -- Esoteric cults and the Saidaiji network: the case of Aizen Myoo -- From Ise to Miwa and beyond -- The Mongol invasions -- Saidaiji order in Ise -- Miwa daimyojin engi -- The authorship of the engi -- Protecting the ancient deities -- Constructing the new sacred geographies -- Part III. Assembling Shinto : Enlightenment for the "country bumpkins" -- Serpent deities and the Buddhist imagination -- Amaterasu as a serpent -- Aizen and medieval "country bumpkins" -- Absorbing the power of kami -- Miwa-ryu Shinto -- Late medieval developments -- Divine regalia and the symbolic rulership -- "Kami abhi?eka, Miwa-style" at Daigorinji -- The kami iconography at Daigorinji -- The divine regalia in the Miwa-ryu rituals -- Edo-period revival of Miwa-ryu Shinto
Includes bibliographical references and index
Keywords: Miwa Mountain Region (Japan) -- Religious life and customs -- History -- To 1500; Geschichte Anfänge-1868; Buddhismus; Synkretismus; Miwa-Shintō; Japan